Morro Bay California [postcard booklet] - Bob Ball::::::::: (Mike Roberts Color Productions)
The booklet includes (001) A front cover of Morro Rock and sailboats at the dock; (002) A back cover of an aerial of Morro Bay; (003) Morro Rock, downtown Morro Bay, back bay; (004) boats and structures near Morro Rock; (005) four views of Morro Rock; (006) fishing boats, bay shore, Morro Rock vista.